ETNOGRAFI KEBUDAYAAN KONSUMSI DI KALANGAN REMAJA PENGGUNA SISTEM BELANJA ONLINE DI PLAMONGANSARI, PEDURUNGAN, SEMARANG - Ziyadatun Nikmah; Riris Tiani (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
This study aims to determine the pattern of consumption culture that is a reference among adolescent users of online shopping systems. The type of research method used is qualitative research with an ethnographic approach. The informants studied were teenagers who used online shopping applications. Data collection techniques with literature study, observation, interviews and documentation. The results of the data that have been obtained are then analyzed with postmodern social theory by Jean Baudrillard. This study shows that online shopping can form a consumptive culture among teenagers, referring to behavioral patterns in shopping that are continuously repeated until it becomes a habit in fulfilling needs and desires. There are two patterns of consumption culture that become a reference among teenagers who use the online shopping system, namely, first, the pattern of simulated consumption culture, which is where teenagers shop online to fulfill their needs and teenagers shop online because of advertisements, promos, and friends. Second, the pattern of hyperreality consumption culture is that teenagers shop online because of trends and lifestyles.